2015
DOI: 10.1093/cercor/bhv127
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recruitment of Dentate Gyrus Interneuron Types by Commissural Versus Perforant Pathways

Abstract: Gamma-aminobutyric acidergic (GABAergic) interneurons (INs) in the dentate gyrus (DG) provide inhibitory control to granule cell (GC) activity and thus gate incoming signals to the hippocampus. However, how various IN subtypes inhibit GCs in response to different excitatory input pathways remains mostly unknown. By using electrophysiology and optogenetics, we investigated neurotransmission of the hilar commissural pathway (COM) and the medial perforant path (MPP) to the DG in acutely prepared mouse slices. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 57 publications
9
118
0
Order By: Relevance
“…Interestingly, CNO-induced responses in dentate GABA neurons were highly heterogeneous (Fig. 3B-D), consistent with the recent finding that the MC commissural pathway preferentially recruits several subsets of dentate GABA interneurons (Hsu et al, 2016). Dentate PV interneurons can functionally interact with and regulate rNSCs (Song et al, 2012), and our Ca2+ imaging showed 32% of the responding cells were from the SGZ where PV basket cells reside (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, CNO-induced responses in dentate GABA neurons were highly heterogeneous (Fig. 3B-D), consistent with the recent finding that the MC commissural pathway preferentially recruits several subsets of dentate GABA interneurons (Hsu et al, 2016). Dentate PV interneurons can functionally interact with and regulate rNSCs (Song et al, 2012), and our Ca2+ imaging showed 32% of the responding cells were from the SGZ where PV basket cells reside (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1A-B). Since GCs and pyramidal cells do not project to the contralateral DG (Hsu et al, 2016), we limited our structural and functional analyses to the contralateral side for specificity. Within the hilus, injection of AAV-CaMKII-mCherry labeled ~82% of GluR2/3+ cells (specific marker for MCs) and ~94% of AAV-CaMKII-mCherry labeled cells were positive for GluR2/3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as DIC prisms are not required, the IR-DGC image can be overlaid with a fluorescence image 49,52,53,76 . Second, DGC can be combined with photostimulation and optogenetics 77 .…”
mentioning
confidence: 99%